2018
DOI: 10.4269/ajtmh.18-0421
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Melioidosis in Patients Receiving Hemodialysis in the Tropics? One Size Does Not Fit All

Abstract: Melioidosis has a high case fatality rate and is more common in patients with chronic kidney disease. Some authors recommended trimethoprim/sulfamethoxazole (TMP/SMX) prophylaxis for all hemodialysis (HD) patients during the wet season in melioidosis-endemic regions. Historical data were reviewed to determine if TMP/SMX prophylaxis was warranted in the HD population of Far North Queensland, Australia. Between 1997 and 2017, there were 242 culture-confirmed cases of melioidosis in the region, three (1.2%) occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…A clinical trial showed that co-trimoxazole on its own was equally as effective as co-trimoxazole and doxycycline during the eradication phase ( 5 ). Oral co-trimoxazole has also been recommended as a prophylactic agent ( 3 ) and was subsequently recommended prophylactically in hemodialysis patients ( 6 ); however, the practicalities of adopting this approach universally have been challenged ( 7 ). Murine studies have shown co-trimoxazole to be efficacious for prophylaxis for inhalational melioidosis ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…A clinical trial showed that co-trimoxazole on its own was equally as effective as co-trimoxazole and doxycycline during the eradication phase ( 5 ). Oral co-trimoxazole has also been recommended as a prophylactic agent ( 3 ) and was subsequently recommended prophylactically in hemodialysis patients ( 6 ); however, the practicalities of adopting this approach universally have been challenged ( 7 ). Murine studies have shown co-trimoxazole to be efficacious for prophylaxis for inhalational melioidosis ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tinea is a pruritic, scaly skin condition transmitted from human to human. Alternatively, it can also be acquired from the environment 1 or household pets, 34 and in northern Australia is caused by Microsporum spp. and Trichophyton spp.…”
Section: Tineamentioning
confidence: 99%
“…There are data to support chemoprophylaxis in selected populations, but the relatively low incidence in even high-risk populations and the potential life-threatening side-effects of TMP-SMZ means that this is likely to have a very limited role in combating the disease. 33,34 Vaccines are under development, although none have yet undergone human trials. 35 Public health strategies to reduce the incidence of predisposing risk factors -or at least optimise their management -might reduce the burden of melioidosis as well as other complications from these comorbidities.…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Public health strategies that focus on human behaviour and aim to prevent exposure to B. pseudomallei are challenging to implement [40,41]. Chemoprophylaxis would not be cost-effective locally and is associated with significant side effects [42]. More comprehensive primary healthcare, with a focus on addressing the comorbidities that…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%